EXILE AND ITS IMPACT ON SHIFTING PERSPECTIVES ON POLITICS, INSTITUTIONS AND COLLECTIVE IDENTITIES - Roniger, Luis (2013)
Exile is an institutionalized mechanism of political exclusion, which has been used throughout Latin America. This article aims to analyze its impact on the reformulation of political and institutional perspectives. It is abroad that citizens forced out of a national territory redefine political commitments and rephrase collective visions, with an impact on the countries of origin. Based on historical and more recent cases of forced displacement, this work stresses the contribution of political exiles to the redefinition of the collective horizons of the Latin American societies.